Comparison between two types of anaerobic speed endurance training in competitive soccer players - Mohr, M.; Krustrup, P. (Journal of Human Kinetics, 2016)
The purpose of the present study was to examine the effects of additional in-season speed endurance production versus speed endurance maintenance training regimes on performance in competitive male soccer players. In a randomised controlled trial 18 male sub-elite players were exposed to additional speed endurance production (SEP) or speed endurance maintenance (SEM) training (two additional sessions/wk for 4 weeks) during the competitive season. Players performed the Yo-Yo intermittent recovery level 2 test (YYIR2) and a repeated sprint test (RST) pre- and post-intervention. Yo-Yo IR2 performance increased (p<0.001) by 50 ± 8% and 26 ± 5% in SEP and SEM, respectively, with greater (p=0.03) improvement in SEP. RST performance improved by 2.1 ± 0.3% and 1.3 ± 0.4% in SEP and SEM, respectively, while the RST fatigue index decreased (4.4 ± 0.8 to 3.4 ± 0.5%; p<0.04) in SEP only. Peak and average speed during training were higher (p<0.001) in SEP than in SEM (24.5 ± 0.3 vs 19.2 ± 0.3 and 15.5 ± 0.1 km·h-1 vs 9.4 ± 0.1 km·h-1). Additional in-season anaerobic speed endurance production and maintenance training improves high-intensity exercise performance in competitive soccer players with superior effects of speed endurance production training.